Relationship between Trigonometry Functions with Hyperbolic Function - Sri Rejeki Dwi Putranti (Alliance of Health Activists (AloHA), 2019)
Many engineering problems can be solved by methods involving complex numbers and complex functions. In the definitions below we will prove the relationship between trigonometric functions and hyperbolic functions, where the hyperbolic function is an extension of the trigonometric function. Keywords: trigonometric functions; hyperbolic functions